The Economics of Public Finance - Blinder, Alan (Rowman & Littlefield Publishers, 2011)
This is the thirty-fifth volume in the Brookings Studies of Government Finance series. In the first of its four essays, Analytical Foundations of Fiscal Policy,” Alan S. Blinder of Princeton University and Robert M. Solow of the Massachusetts Institute of Technology survey the theoretical and empirical underpinnings of fiscal policy. After discussing how the influence of fiscal policy on macroeconomic activity ought to be assessed, the authors examine and find inadequate the dictum that government should balance the budget rather than the economy. They defendagain both theoretically and empiricallythe efficacy of fiscal policy against the monetarist challenge. From an examination of the lags and uncertainties in the operation of fiscal policy and an analysis of the 196870 income tax surcharge, they conclude that, although much remains to be learned about the econometrics of policy multipliers, the post-surcharge experience in no way undermines the theoretical foundations of fiscal policy. Where the burdens of various taxes fall has been a matter of intense interest to economic theorists in the last twenty years. As public expenditures (and taxpayer resistance) rise, not only must policy makers try to distribute the burdens of taxation equitably, but they must also attempt to move toward national goals by judicious use of tax instruments. George F. Break of the University of California at Berkeley, in The Incidence and Economic Effects of Taxation,” a comprehensive review of recent tax literature, focuses on the theoretical studies that have helped to expand knowledge of tax incidence and the empirical studies that support newly developed hypotheses. In each area he surveysthe design of theoretical and general sales and income taxes; the effect of economic choices, both of individuals and businesses, on the national well-beingBreak indicates the ground still to be covered and the potential benefits of further inquiry. In Public Expenditure Budgeting,” Peter O. Steiner of the University of Michigan explores the literature dealing with the hard questions underlying public expenditures. What is the public interest? How does the community decide whether the government should undertake or finance a given activity, instead of leaving it to a private action or inaction? On what basis should incremental expenditure decisions of governmental units be made? Steiner reviews the various approaches scholars have taken to the difficult questions surrounding the appropriateness of governmental provision of particular goods and services. Although he finds none of the models fully satisfactory, his work contributes to the debate concerning the process by which collective values are articulated and collective decisions come to be accepted as binding. Dick Netzer’s State-Local Finance and Intergovernmental Fiscal Relations” clarifies the debate that centered around the initial proposals for revenue sharing. The author, Dean of New York University’s Graduate School of Public Administration, explores the appropriate distribution of responsibility for public services among federal, state, and local governments, the appropriate revenue systems for the subnational governments, and the appropriate means of coordinating the systems with the responsibilities.